SEVTAR—A multicenter randomized controlled trial to investigate the impact of prophylactic endoluminal placed vacuum sponge for prevention of anastomotic leakage after low rectal resections - Schiffmann, Leif; Becker, Matthias; Develing, Leendert; Varga-Szabo, David; Scheidereiter-Krüger, Caroline; Zirngibl, Hubert; Seifert, Michael; Biermann, Lothar; Schlüter, Claudia; Tumczak, Felicitas; Weimann, Arved; Jansen-Winkeln, Boris; et al. (Frontiers in Surgery, 2023)
Background: Low anterior resection for rectal cancer is commonly associated with a diverting stoma. In general, the stoma is closed three months after the initial operation. The diverting stoma reduces the rate of anastomotic leakage as well as the severeness of a potential leakage itself. Nevertheless, anastomotic leakage is still a life-threatening complication and might reduce the quality of life in the short and long term. In case of a leakage, the construction can be converted into a Hartmann situation or it could be treated by endoscopic vacuum therapy or by leaving the drains. In recent years, endoscopic vacuum therapy has become treatment of choice in many institutions. In this study, the hypothesis is to be evaluated, if a prophylactic endoscopic vacuum therapy reduces the rate of anastomotic leakage after rectal resections. Methods: A multi-centre parallel group randomised controlled trial (RCT) is planned in as many as possible centres in Europe. The study aims to recruit 362 analyzable patients with a resection of the rectum combined with a diverting ileostoma. The anastomosis has to be between 2 to 8 cm off ACL. Half of these patients receive a sponge for 5 days, the control group is treated as usual in the participating hospitals. There will be a check for anastomotic leakage after 30 days. Primary end point is the rate of anastomotic leakages. The study will have 60% power to detect a difference of 10%, at a one-sided alpha significance level of 5%, assuming an anastomosis leakage rate of 10 to 15%. Discussion: If the hypothesis proofs to be true, anastomosis leakage could be reduced significantly by placing a vacuum sponge over the anastomosis for 5 days. Trial registration: The trial is registered at DRKS: DRKS00023436. It has been accredited by Onkocert of the German society of cancer: ST-D483. The leading Ethics Committee is the Ethic Committee of Rostock University with the registration ID: A 2019–0203.